PENGARUH CSR INTERNAL DAN CSR EKSTERNAL TERHADAP KEPUASAN KERJA KARYAWAN (Studi pada PT. Phapros, Tbk) - Lestari, Laras Puspa; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2018)
The application of CSR becomes something that should be done for the company because it has been regulated in the law. The company undertakes various strategies among them to implement CSR aimed at increasing job satisfaction. CSR has three aspects: social, economic, and environmental aspects. This research is motivated by the research gap from previous studies, and it is known that there is a decline in the employee job satisfaction. This research aims to analyze the influence of internal CSR and external CSR on job satisfaction.Data collected from population amounted to 92 employees with sampling using total sampling amounted to 92 respondents who work as employee at PT. Phapros, Tbk in section of accounting, finance, CSR, HRD and general, and risk management. Analysis of the data in this study using multiple linear regression techniques, and sobel test, to test the mediating effect, using SPSS program. The results showed, Internal CSR variabel positively affect onÂ employee job satisfaction. Eksternal CSR has no effect onÂ employee job satisfaction.